Parvovirus B19 infection in pregnancy - Laura Dumitrasi; Radu Botezatu; Nicolae Gica; Anca Marina Ciobanu; Corina Gica; Brindusa Ana Cimpoca; Gheorghe Peltecu; Anca Maria Panaitescu (Romanian Medical Journal, 2020)
Parvovirus B19 infection is the most common cause of non-immune hydrops in fetuses. The risk of congenital infection is highest in the 1st and 2nd trimester and there are no current recommendations regarding screening of low-risk pregnancies. Recent exposure of the mother and ultrasound findings of fetal anemia or hydrops should include parvovirus B19 infection investigation. Adequate monitoring through ultrasound and Doppler determine the fetal and perinatal outcome as interventions as intrauterine blood transfusions are the main treatment.